Development of physical fitness test for mild intellectual disabilities aged 13-15 years - Sumaryanti Sumaryanti; Sigit Nugroho; Aqim Visalim; Japhet Ndayisenga (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
This study aims to compile a physical fitness test for mild intellectual disability, test the suitability of the test in terms of suitability, convenience, and safety. The developed tests consist of a bench up and down test, a lying down test, a sitting test and a body mass index test. The stages of development carried out include planning stage, preparation stage, trial, evaluation and revision, and final product. The experimental subjects in this study were children with mild intellectual disabilities aged 13-15 years, totaling 148 people who were divided into limited trial subjects, expanded trial subjects, and validity and reliability test subjects. Validity data analysis technique with two tests using the composite score method and using Doolittle analysis, and reliability data analysis using alpha coefficient analysis. Based on the results of the study, a set of tests was obtained to measure the physical fitness of persons with mild intellectual disabilities with very high validity and reliability tests, where the validity of the test for boys is 0.968 and for girls is 0.914. While the test reliability value for men is 0.896 and for women is 0.883. The physical fitness test was developed according to the characteristics of mild mental retardation which included components on cardiovascular endurance, muscle strength and endurance, flexibility, and body composition.